Immunohistochemical markers of prognosis in adult granulosa cell tumors of the ovary - a review - Dennis Jung; Katrin Almstedt; Marco J. Battista; Alexander Seeger; Jörg Jäkel; Walburgis Brenner; Annette Hasenburg (BMC, 2023)
Abstract Background Granulosa cell tumors (GCT) are rare malignant ovarian tumors. The two subtypes, adult and juvenile granulosa cell tumors, differ in clinical and molecular characteristics. GCT are low-malignant tumors and are generally associated with favorable prognosis. However, relapses are common even years and decades after diagnosis. Prognostic and predictive factors are difficult to assess in this rare tumor entity. The purpose of this review is to provide a comprehensive overview of the current state of knowledge on prognostic markers of GCT to identify patients with a high risk of recurrence. Methods Systematic research for adult ovarian granulosa cell tumors and prognosis revealed n = 409 English full text results from 1965 to 2021. Of these articles, n = 35 were considered for this review after title and abstract screening and topic-specific matching. A specific search for pathologic markers with prognostic relevance for GCT identified n = 19 articles that were added to this review. Results FOXL2 mutation and FOXL2 mRNA were inverse and immunohistochemical (IHC) expression of CD56, GATA-4 and SMAD3 was associated with reduced prognosis. IHC analysis of estrogen receptor, Anti-Mullerian hormone (AMH) and inhibin was not associated with prognosis for GCT. Analyses of mitotic rate, Ki-67, p53, β-catenin and HER2 revealed inconsistent results.